Costos Aplicados a la Producción Bananera de la Hacienda Fátima - Valencia Jurado, Joselin Karina (2018)
The following case study is carried out at Hacienda Fátima, located at km 2.2 of the Baba Tinoco road, for which several visits were made to both the administrative areas and the operational areas; In order to obtain the information, information gathering instruments were designed, that is to say: interviews to the personnel of the administrative area, observation in the operational areas, review of pertinent documents in which the tape count registration is done, which is the current control system that takes the hacienda. For (FERNANDEZ, 2016) ". The difference between an industrial and a banana plantation is that its costs are affected by the proliferation of pests, climatic changes that affect costs because they are greatly increased, causing that in many cases suppliers have to assume large costs that do not compensate the values ​​paid "(page 17). The Fátima farm, object of the case study, is dedicated to the cultivation, production and marketing of fruit such as bananas.